INTAKE AND APPARENT DIGESTIBILITY OF Andropogon gayanus HAY AT THREE DIFFERENT AGES - Cavalcanti, André Cayô (2016)
The aim of this study was to evaluate the voluntary intake and apparent digestibility of dry matter, crude protein, fiber fractions, energy, and the nitrogen balance of Andropogon gayanus hay at three different stages (56, 84 and 112 days). The statistical design was completely randomized, with three treatments and six replicates. Dry matter, fiber fractions, and energy apparent digestibility were higher (P<0.05) for hay harvested at 56 and 84 days. Crude protein intake and apparent digestibility of A. gayanus hay harvested at 56 days of growth were greater (P<0.05) than the hay harvested at 84 and 112 days. The A. gayanus hay showed the best voluntary intake and digestibility at 56 and 84 days of age.Keywords: forage; nutritive value; sheep.